E-143 Endovascular treatment for symptomatic intracranial atherosclerotic stenosis. (22nd July 2018) - Ueda, T; Takada, T; Takaishi, S; Usuki, N; Tokuyama, Y; Fukano, T; Tatsuno, K; Hamada, Y
Abstract : Purpose: Intracranial atherosclerotic stenosis (ICS) is an important cause of ischemic stroke, particularly in the Asian population. Endovascular treatment, such as balloon angioplasty with and without stenting have emerged as therapeutic options for symptomatic (ICS) since the 1990s and the Wingspan stent was approved at 2014 in Japan. This study was to investigate the periprocedural complication rates, long-term outcome and restenosis of endovascular treatment for ICS in our hospital. Methods: We retrospectively analyzed the clinical data of 217 patients with 256 endovascular treatments for high-grade symptomatic ICS between 1999 and 2017. The lesion was located in in the internal carotid artery in 77, the middle cerebral artery in 111, the basilar artery in 29 and the vertebral artery in 39. Patients were divided into two groups, before (A group, between 1999 and 2013) and after approval of Wingspan (B group, between 2014 and 2017). We assessed perioperative and long-term outcomes such as restenosis and the recurrence of strokes. Results: In A group (n=163, aged 63.5±10.2 years), 157 lesions were treated with balloon angioplasty and 31 (16.5%) with coronary stent. In B group (n=54, aged 66.4±13.3 years), 33 lesions were treated with balloon angioplasty and 35 (51.5%) with Wingspan stent. Overall technical success rates were 96% in balloon angioplasty and 100% in stenting groups. The 30 day rate of stroke, TIA and death were 4.3% in A group and 4.4% in B group. In B group, there was one patient who had subacute in-stent thrombosis with major stroke and 2 minor stroke. There were no stroke and vascular events during follow-up periods in B group. Eight patients (14.8%) in B group had restenosis after the procedure and 7 patients were retreated. Conclusions: This study demonstrates the safety and efficacy of balloon angioplasty with and without stenting for symptomatic intracranial atherosclerotic stenosis if patients are properly selected. We suggest that a more judicious use of intracranial stents may be responsible for better postprocedure outcome. Disclosures: T. Ueda: None. T. Takada: None. S. Takaishi: None. N. Usuki: None. Y. Tokuyama: None. T. Fukano: None. K. Tatsuno: None. Y. Hamada: None.